(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
The communication aspects analysis of the informing in the mass media movies into several directions. First, mass media as part of the social reality play a significant role in the public informing of all its segments. Second they follow and present information through certain forms of informing that evoke different effects at the audience. Those effects present the quality and development of the media itself.